El Perú actual es más nacional porque es más indígena - Manuel Burga; Pablo Macera (Les Cahiers ALHIM)
From the dialogs between the two historians Pablo Macera and Manuel Burga, came to surface big themes of the Peruvian history. Pablo Macera refers to the becoming of the republic and concludes establishing a major indianization of Peru.